Comprehensive overexpression analysis of cyclic-di-GMP signalling proteins in the phytopathogen Pectobacterium atrosepticum reveals diverse effects on motility and virulence phenotypes - Tan, H.; West, J.; Ramsay, Joshua; Monson, R.; Griffin, J.; Toth, I.; Salmond, G. (Society for General Microbiology, 2014)
Bis-(3′-5′)-cyclic dimeric guanosine monophosphate (c-di-GMP) is a ubiquitous bacterial signalling molecule produced by diguanylate cyclases of the GGDEF-domain family. Elevated c-di-GMP levels or increased GGDEF protein expression is frequently associated with the onset of sessility and biofilm formation in numerous bacterial species. Conversely, phosphodiesterase-dependent diminution of c-di-GMP levels by EAL- and HD-GYP-domain proteins is often accompanied by increased motility and virulence. In this study, we individually overexpressed 23 predicted GGDEF, EAL or HD-GYP-domain proteins encoded by the phytopathogen Pectobacterium atrosepticum strain SCRI1043. MS-based detection of c-di-GMP and 5′-phosphoguanylyl-(3′-5′)-guanosine in these strains revealed that overexpression of most genes promoted modest 1–10-fold changes in cellular levels of c-di-GMP, with the exception of the GGDEF-domain proteins ECA0659 and ECA3374, which induced 1290- and 7660-fold increases, respectively.Overexpression of most EAL domain proteins increased motility, while overexpression of most GGDEF domain proteins reduced motility and increased poly-β-1,6-N-acetyl-glucosamine-dependent flocculation. In contrast to domain-based predictions, overexpression of the EAL protein ECA3549 or the HD-GYP protein ECA3548 increased c-di-GMP concentrations and reduced motility. Most overexpression constructs altered the levels of secreted cellulases, pectinases and proteases, confirming c-di-GMP regulation of virulence in Pe. atrosepticum. However, there was no apparent correlation between virulence-factor induction and the domain class expressed or cellular c-di-GMP levels, suggesting that regulation was in response to specific effectors within the network, rather than total c-di-GMP concentration. Finally, we demonstrated that the cellular localization patterns vary considerably for GGDEF/EAL/HD-GYP proteins, indicating it is a likely factor restricting specific interactions within the c-di-GMP network.